NORMALIZATION BASED ON THICKNESS AND PARAMETRIZATION OF CONTOUR LINES ON IMAGES - A. G. Shauchuk; D. I. Kiryliuk; E. G. Makeichyk; V. Yu. Tsviatkou (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The method of normalization of planimetric lines on thickness based on the mask analysis of local orientations of their fragments is offered. Comparison of the offered method with known methods of a skeletization is made. It is shown that the offered method surpasses known methods of a skeletization in speed and quality. Approaches to parametrization of curves are considered.